Flexible MOF on CoXFe1-XOOH@Biomass derived Alloy@Carbon films for efficient electromagnetic interference shielding and energy conversion. (31st October 2022) - Bai, Wenhao; Zhai, Jianyu; Zhou, Shengguo; Cui, Ce; Wang, Weijie; Jiang, Shan; Cheng, Cheng; Ren, Erhui; Xiao, Hongyan; Zhou, Mi; Zhang, Jinwei; Guo, Ronghui
Abstract: Increasingly serious electromagnetic pollution makes efficient electromagnetic shielding more important. Herein, the CoX Fe1-X OOH nanoneedles were creatively synthesized by hydrothermal method and firmly anchored on cotton fabric. Subsequently, CoFe/CoCu-PDMS-carbon films (CoFe/CoCu-PCFs) were prepared by in-situ growth CoCu MOF along CoX Fe1-X OOH nanoneedles, annealing, encapsulating by diluted PDMS. CoX Fe1-X OOH derived interlinked CoFe alloy conductive network. 2D leaf-like CoCu MOF nanosheets grow along 1D CoX Fe1-X OOH nanoneedles, forming a unique "leaf-branch" protection mechanism to inhibit the shrink of composites. Intertwined CoFe/CoCu alloy-carbon fiber with skin-core structure forms double conductive network, which reduces the density and strengthens the absorption during multiple reflection of electromagnetic waves. As results, CoFe/CoCu-PCF-45 (CoCu MOF growing for 45 min) shows the average electromagnetic interference shielding efficiency (EMI SE), SE/t (thickness) and SSE (SE/density)/t reaching 73.46 dB, 3296.62 dB/cm and 12227.21 dB cm 2  g −1, respectively. CoFe/CoCu-PCF-45 maintains high-level shielding performance (>60 dB) after bending 600 cycles at 90°, ultrasonic damage for 3 h and acid/alkali/salt corrosion for 12 h. In addition, CoFe/CoCu-PCF-45 possesses efficient, fast and stable energy conversion (over 150 °C in 10 s at 0.8 V voltage, over 70 °C in 3 s at 0.3 W cm −2 illumination intensity). This work provides new ideas for designing efficient EMI shielding composites. Graphical abstract: Image 1 Highlights: The CoX Fe1-X OOH nanoneedles were creatively synthesized by hydrothermal method. Metallic hydroxyl oxide was first applied for EMI shielding. 2D leaf-like CoCu MOF nanosheets grow along CoX Fe1-X OOH nanoneedles, forming a unique "leaf-branch" protection mechanism. EMI SE and SSE/t of CoFe/CoCu-PCF-45 reach 73.46 dB and 12227.21 dB cm 2  g −1 . CoFe/CoCu-PCF-45 possesses efficient, fast and stable energy conversion.